Mengatasi Kesulitan Menulis Artikel Ilmiah Melalui Kegiatan Academic Writing Series - Jubba, Hasse; Saka, Putri Ananda; Qodir, Zuly; Hidayati, Mega; Pabbajah, Mustaqim; Dzinnun, Yusriah (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
The difficulty of writing and publishing scientific articles in reputable journals is something that is often experienced by academics, especially in universities. Various difficulties are experienced, ranging from language, time, cost, and access to literature expressed by those who have been difficult to realize their obligations. This Academic Writing Series (AWS) activity aims to not only increase the knowledge of academics about the world of writing, but also share strategies so that they are more likely to write and publish their scientific articles. This activity is carried out online through zoom meetings for 10 meetings held every week. Participants responded well to AWS activities as indicated by statements regarding the organization and materials presented. From this activity, it is known that the basic needs of academics regarding writing strategies and scientific publications still need to be improved. Academics' knowledge of how to write easily and effectively is also still limited. AWS activities framed in community service emphasize that various strategies are needed in an effort to improve the writing skills of academics so that they are able to disseminate their research results more widely through publications in reputable journals. This activity is only carried out through online media so it needs to be complemented by face-to-face meetings so that interaction can be maximally realized both between presenters and participants and among fellow academics involved in this AWS activity